Shock response of polymer-bonded copper powder - Anastacio, A. C; Braithwalte, C; Kučera, Jindřich; Schmidová, Eva; Pachman, Jiří (Springer, 2020)
The shock response of a polymer-bonded copper powder was investigated by means of plate impact experiments in a gas gun (pressure range 1-8 GPa) and using in-contact explosive loading (pressures up to 37 GPa). Stress gauges were used to determine the material shock states in the planar impact, and the experimental data of shock and particle velocities (U, u) were fitted to a straight line giving a Hugoniot equation of state U=(0.85 +/- 0.08)+(2.64 +/- 0.05). In the explosive loading experiments, the shock speed in the material was measured using optical methods, and impedance matching was performed to determine the shock state in the sample. Comparison between the two experiments shows that the states attained in the lower-pressure range (planar impact experiments) and higher-pressure range (explosive loading) follow the same Hugoniot curve, within 4% deviation.
Rázová odezva polymerem pojeného měďěného prášku
Keywords: shock load; hugoniot; polymer-bonded metal; linear charges; rázové zatížení; hugoniota; kov spojený polymerem; táhlé nálože